2021
DOI: 10.1080/15257770.2021.1872794
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel pyrimidine thioglycosides as structural analogs of favipiravir (avigan) and their antibird flu virus activity

Abstract: Novel class of amino pyrimidine thioglycoside derivatives were designed from sodium 2-cyano-3-(arylamino)prop-1-ene-1,1bis(thiolate) 1a-d and guanidine hydrochloride 2 to afford the corresponding sodium 2,6-diamino-5-aryl-1,2-dihydropyrimidine-4-thiolate 3a-d, which in coupling with peracylated a-Dgluco-and galactopyranosyl bromides 5a,b in DMF gave the corresponding pyrimidine thioglycosides 6a-h. Acidification of 2,6-diamino-5-aryl-1,2-dihydropyrimidine-4-thiolate salts 3a-d with hydrochloric acid formed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…It is worth noticing that joining two or more diverse heterocyclic rings into one structure may bring about new compounds with upgraded bioactivity . As an example, pyridines with the benzothiazole moiety have enhanced antibacterial and antifungal activities. , To achieve this goal, new strategies for synthesizing pyridine-bearing benzothiazole moieties have been generated. As a continuation of our previous work on the synthesis of bioactive heterocyclic ring systems, we herein report that the cytotoxic activity of some novel arylpyridines incorporated benzothiazole moieties 8a – h against H5N1, SARS-COV-2 viruses, and their inhibition of SARS-COV-2 main protease (M pro ). Molecular docking studies of more potent main protease inhibitors were also performed to find a potential candidate as antiviral agent toward H5N1 and SARS-CoV-2 viruses.…”
Section: Introductionmentioning
confidence: 77%
“…It is worth noticing that joining two or more diverse heterocyclic rings into one structure may bring about new compounds with upgraded bioactivity . As an example, pyridines with the benzothiazole moiety have enhanced antibacterial and antifungal activities. , To achieve this goal, new strategies for synthesizing pyridine-bearing benzothiazole moieties have been generated. As a continuation of our previous work on the synthesis of bioactive heterocyclic ring systems, we herein report that the cytotoxic activity of some novel arylpyridines incorporated benzothiazole moieties 8a – h against H5N1, SARS-COV-2 viruses, and their inhibition of SARS-COV-2 main protease (M pro ). Molecular docking studies of more potent main protease inhibitors were also performed to find a potential candidate as antiviral agent toward H5N1 and SARS-CoV-2 viruses.…”
Section: Introductionmentioning
confidence: 77%
“…More potent activities were found for compounds 39 and 40 at 0.25 μM concentration against H5 N1 (83 % and 86 % inhibition) and IC 50 values of 12.16 μM for 39 and 14.9 μM for 40 against SARS‐CoV‐2; These compounds were selective for SARS‐CoV‐2, with SI indices of 28.2 and 26.9, for 39 and 40 respectively. Abu‐Zaied and colleagues also previously developed novel favipiravir (Avigan ® ) pyrimidine thioglycoside analogues [41] active against the avian influenza virus (H5 N1). Compounds 41 , 42 , 43 , 44 and 45 showed inhibitions of 75, 75, 77, 78.83 and 83 %, respectively, at a concentration of 0.25 μM (Figure 18).…”
Section: Resultsmentioning
confidence: 99%
“…Among series of novel compounds, (7 a-d) have displayed potent to moderate antiviral activity (Scheme 8). [127] El Mansouri et al have reported synthesis and furo[2,3d]pyrimidine-1,3,4-oxadiazole hybrids as antiviral and anticancer agents. They prepared final compounds (65a-d) starting from (58a-d) via Songoashira-heterocyclization in presence of nanostructured palladium pyrophosphate (Na 2 PdP 2 O 7 ).…”
Section: Chemistryselectmentioning
confidence: 99%
“…Among series of novel compounds, ( 7 a – d ) have displayed potent to moderate antiviral activity (Scheme 8). [127] …”
Section: Pyrimidine Analogs As Antiviral Agentsmentioning
confidence: 99%